2018
DOI: 10.3847/1538-4357/aae2bc
|View full text |Cite
|
Sign up to set email alerts
|

Hyperflares of M Dwarfs

Abstract: From a study of the light curves of the M dwarfs observed by the Kepler space telescope in its primary mission, a number of flare events with the peak flux increases reaching more than the nominal stellar luminosity have been found. One of them, KIC 9201463, produced an extreme flare with the peak flux increase jumping to five times the quiet-time value. In relative terms, this class of hyperflares is much stronger than the superflares of the solar-type stars and could have a very important influence on the at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The TESS sample profits from the mission's observing strategy, allowing us to identify 112 flaring stars with 141 individual flares that fulfill the Chang et al (2018) criterion of at least doubling the stellar brightness. A list of these targets can be created from Table 1 by sorting by the amplitude column.…”
Section: Stars Show Flares With Flux Increases Of Multiple Magnitmentioning
confidence: 99%
See 2 more Smart Citations
“…The TESS sample profits from the mission's observing strategy, allowing us to identify 112 flaring stars with 141 individual flares that fulfill the Chang et al (2018) criterion of at least doubling the stellar brightness. A list of these targets can be created from Table 1 by sorting by the amplitude column.…”
Section: Stars Show Flares With Flux Increases Of Multiple Magnitmentioning
confidence: 99%
“…If only the T eff is available, we esti- The flare luminosity is modeled as black body radiation with an effective temperature of 9000 K. We select (9000 ± 500) K as a conservative lower limit to remain consistent with other studies (e.g. Davenport 2016;Jackman et al 2018b,a;Howard et al 2018;Chang et al 2018).…”
Section: Measuring the Flare Energymentioning
confidence: 99%
See 1 more Smart Citation
“…An understanding of their variability is needed to set limits on the threshold for a signature in the signal of a true transit event. Recently Chang et al (2018) analyzed evem more extreme hyperflares in Kepler data for M dwarf stars and noted 8 of them in the K1 lightcurve database. In the course of our study of Proxima Centauri, we found one very large flare that may qualify as a super flare and certainly sets a limit on the frequency of its more extreme flares.…”
Section: Observations Of Proxima Centaurimentioning
confidence: 99%
“…There was significant evidence for superflares and solar flares to most likely share the same origin, and robust estimates of the relationship between chromospheric activity and the occurrence of superflares were presented. On the other hand, studies of flaring M dwarfs in the Kepler field have been presented in several articles by using both satellite photometry and LAMOST data (Yang et al 2017;Chang et al 2017Chang et al , 2018Lu et al 2019). Using Kepler and LK project data, research progress was reported on the chromospheric activity of periodic variable stars (Zhang et al 2018b) and long-rotation-period main-sequence stars (Cui et al 2019).…”
Section: Stellar Magnetic Activity and Flaresmentioning
confidence: 99%